Low-Temperature Reduction of Graphene Oxide: Electrical Conductance and Scanning Kelvin Probe Force Microscopy - Oleksandr M. Slobodian; Peter M. Lytvyn; Andrii S. Nikolenko; Victor M. Naseka; Oleg Yu. Khyzhun; Andrey V. Vasin; Stanislav V. Sevostianov; Alexei N. Nazarov (Nanoscale Research Letters, 2018)
Abstract Graphene oxide (GO) films were formed by drop-casting method and were studied by FTIR spectroscopy, micro-Raman spectroscopy (mRS), X-ray photoelectron spectroscopy (XPS), four-points probe method, atomic force microscopy (AFM), and scanning Kelvin probe force (SKPFM) microscopy after low-temperature annealing at ambient conditions. It was shown that in temperature range from 50 to 250 °C the electrical resistivity of the GO films decreases by seven orders of magnitude and is governed by two processes with activation energies of 6.22 and 1.65 eV, respectively. It was shown that the first process is mainly associated with water and OH groups desorption reducing the thickness of the film by 35% and causing the resistivity decrease by five orders of magnitude. The corresponding activation energy is the effective value determined by desorption and electrical connection of GO flakes from different layers. The second process is mainly associated with desorption of oxygen epoxy and alkoxy groups connected with carbon located in the basal plane of GO. AFM and SKPFM methods showed that during the second process, first, the surface of GO plane is destroyed forming nanostructured surface with low work function and then at higher temperature a flat carbon plane is formed that results in an increase of the work function of reduced GO.